Long-term supratentorial brain structure and cognitive function following cerebellar tumour resections in childhood. (March 2015) - Moberget, T.; Andersson, S.; Lundar, T.; Due-Tønnessen, B.J.; Heldal, A.; Endestad, T.; Westlye, L.T.
Abstract: The cerebellum is connected to extensive regions of the cerebrum, and cognitive deficits following cerebellar lesions may thus be related to disrupted cerebello-cerebral connectivity. Moreover, early cerebellar lesions could affect distal brain development, effectively inducing long-term changes in brain structure and cognitive function. Here, we characterize supratentorial brain structure and cognitive function in 20 adult patients treated for cerebellar tumours in childhood (mean age at surgery: 7.1 years) and 26 matched controls. Relative to controls, patients showed reduced cognitive function and increased grey matter density in bilateral cingulum, left orbitofrontal cortex and the left hippocampus. Within the patient group, increased grey matter density in these regions was associated with decreased performance on tests of processing speed and executive function. Further, diffusion tensor imaging revealed widespread alterations in white matter microstructure in patients. While current ventricle volume (an index of previous hydrocephalus severity it patients) was associated with grey matter density and white matter microstructure in patients, this could only partially account for the observed group differences in brain structure and cognitive function. In conclusion, our results show distal effects of cerebellar lesions on cerebral integrity and wiring, likely caused by a combination of neurodegenerative processes and perturbed neurodevelopment. Highlights: We investigated long-term structural and functional effects of cerebellar lesions. Relative to controls, cognitive function was reduced in cerebellar patients. Diffusion tensor imaging showed widespread alterations in cerebral white matter. Voxel-based morphometry revealed increased grey matter density in cingulate cortex. Increased grey matter density was associated with decreased cognitive function.